Desain Sistem Informasi Rekam Medis Indeks Penyakit Dengan Metode Agile - Adellia Permatasari Hartono; Yuda Syahidin .; Irda Sari . (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This study aims to find out as well as simplify and speed up officers in processing patient data and preparing reports, designing an information system for emergency room patient visits also intends to process patient data more quickly and effectively. This study uses a qualitative method with a descriptive approach. The data collection technique used is by means of observation, interviews, and supplemented by literature study. While the development method uses agile methods. The problems found in this study are: There is no information system for emergency patient visits, the patient visit data for emergency departments is still filled in using Microsoft Excel. With the creation of this information system, officers can process patient data quickly and easily because the computerized system is more organized and better integrated than before.